Pemanfaatan Website UMKM Unggulan Desa Karangbendo Kabupaten Banyuwangi sebagai Sarana Penunjang Kegiatan Promosi - Ratri, Indira Nuansa; Ratri, Arum Andary; Prasetyo, Junaedi Adi; Fahrurrozi, Rahmad; Rentianto, Tresnarai Juniarizky (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Karangbendo Village is one of the villages in Banyuwangi whose income is based on Village Land, Self-Help Results, and Community Participation. The problems experienced by partners based on the results of the situation analysis that has been carried out include: Marketing of the Leading UMKM association is still traditional, minimal knowledge about strategies to increase brand awareness, and the absence of a profile of the Leading UMKM association for marketing activities. Based on several problems experienced, the service team proposed several solutions for partners, namely: creating a website for the Leading UMKM of Karangbendo Village and providing training for website content fillers collectively at five Leading UMKM of Karangbendo Village. To implement this solution, the service team carried out several methods, including: Implementation method for creating a website for the Leading UMKM association of Karangbendo Village, implementation method for making a video for the Leading UMKM association of Karangbendo Village, monitoring and evaluating activities, and partner participation in the implementation process. This series of activities resulted in an integrated website that can be accessed by all interested parties containing information about the leading UMKM of Karangbendo Village, be it products, locations or contacts that can be contacted which can later increase brand awareness for each leading UMKM.